2019
DOI: 10.1002/chem.201805686
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Ion Tuning in Triple‐Stranded Helicate‐Based Metallosupramolecules

Abstract: Effective incorporation of multiple types of ligands in a given coordination structure provides structural complexity and functional diversity to the resultant coordination‐driven assembly. One of the most widely used synthetic approaches is the utilization of the molecular symmetry principle to combine multiple ligands and specific metallic centers in a preferred manner. The variation of metal ions can be helpful to understand the importance of symmetry for the generation of structurally hierarchical supramol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Note that the coordinated solvents in terminal nickels may not be the same in every experiment. The metal clusters possess chirality, either clockwise or counterclockwise, which is similar to the reported structures. Each discrete supramolecule of 1 is constructed from two metal clusters with opposite chirality, resulting in a meso-helicate (Figure ). The existence of one mirror plane of symmetry passing through the middle point of the three CH 3 -TP ligands initiates C 3h symmetry of the meso-helicate.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…Note that the coordinated solvents in terminal nickels may not be the same in every experiment. The metal clusters possess chirality, either clockwise or counterclockwise, which is similar to the reported structures. Each discrete supramolecule of 1 is constructed from two metal clusters with opposite chirality, resulting in a meso-helicate (Figure ). The existence of one mirror plane of symmetry passing through the middle point of the three CH 3 -TP ligands initiates C 3h symmetry of the meso-helicate.…”
Section: Resultssupporting
confidence: 75%
“… 42 , 43 The oxidation state of nickel ions was determined to be +2 by the presence of two strong peaks at 855.98 and 873.11 eV standing for Ni 2p 3/2 and Ni 2p 1/2 , respectively ( Figure S7d ). 35 , 36 The bond valence sum calculation also revealed that nickel ions in these clusters have a +2 oxidation state ( Table S2 ). 44 , 45 The measurement of temperature-dependent magnetization (emu/g) of 1 was conducted using a Quantum Design MPMS3 magnetometer for temperatures 3 K ≤ T ≤ 300 K with 1000 Oe applied fields ( Figure S8a ).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations